The Role of Teachers in Utilizing ChatGPT to Create Numeracy Literacy Teaching Media at TK BSC School - Nurkamisah Nurkamisah; Imamah Imamah (Dinasti Publisher, 2024)
This research aims to investigate the role of teachers in developing numeracy literacy teaching media using ChatGPT. The effectiveness of using ChatGPT as an aid in creating numeracy literacy teaching media at TK BSC School is also examined, with the goal of capturing children's interest and engagement. This study employs a descriptive qualitative research design. The subjects consist of 25 respondents, comprising 83% with a bachelor's degree education level, including teachers, principals, and parents. Approximately 53% of the teachers have more than 5 years of teaching experience. Data collection techniques include observation, interviews, and questionnaires. Data analysis utilizes triangulation techniques involving data reduction, presentation, and drawing conclusions. The research findings indicate that teachers feel significantly assisted, with approximately 55.3% stating that ChatGPT is beneficial and provides additional material options for creating numeracy literacy teaching media. Additionally, respondents report feeling comfortable using ChatGPT and are able to spend extended periods of time in front of the computer due to their increasing curiosity about the responses generated by ChatGPT.